Reconstructing gene regulatory networks from knock-out data using Gaussian Noise Model and Pearson Correlation Coefficient - Mohamed Salleh F.H.; Arif S.M.; Zainudin S.; Firdaus-Raih M. (Elsevier Ltd, 2023)
Bioinformatics; Correlation methods; Gaussian distribution; Gaussian noise (electronic); Genes; DREAM; Gaussian model; Gene regulatory networks; Pearson correlation coefficients; Probability and statistics; Complex networks; algorithm; biological model; biology; gene inactivation; gene regulatory network; genetics; human; Algorithms; Computational Biology; Gene Knockout Techniques; Gene Regulatory Networks; Humans; Models, Genetic